2017
DOI: 10.21701/bolgeomin.128.3.010
|View full text |Cite
|
Sign up to set email alerts
|

Geology applied to the study of seismic microzoning of Santiago de los Caballeros, Dominican Republic

Abstract: After the Haiti quake of 2010 an initiative started to better understand shaking effects in the Dominican Republic after natural earthquakes, in particular in the city of Santiago de los Caballeros, the second city in the country as far as inhabitants and economic wealth are concerned. Santiago has suffered several devastating earthquakes; in 1562 the city was rebuilt on a new site (the current location) further south from the responsible fault. It is well known that damage caused by an earthquake occurs assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The presence of a regular velocity gradient in these Quaternary clays, characterized by poor mechanical properties (a shear-wave velocity of 240 m/s), may explain the inability of the HVSR method to detect significant site effects. Moreover, the probable low velocity contrast between this clayey formation at depth and the bedrock, expected at around 100 m [22], may explain underestimation of the HVSR peak amplitude, as suggested in previous studies using the HVSR technique [23][24][25]. Modeling the ambient-noise wavefield, Reference [24] have observed that the amplitude of HVSR peaks also depends on the relative contribution of different types of seismic waves (body and surface waves).…”
Section: Site Characterization-examples From Santo Domingo and Santiamentioning
confidence: 90%
“…The presence of a regular velocity gradient in these Quaternary clays, characterized by poor mechanical properties (a shear-wave velocity of 240 m/s), may explain the inability of the HVSR method to detect significant site effects. Moreover, the probable low velocity contrast between this clayey formation at depth and the bedrock, expected at around 100 m [22], may explain underestimation of the HVSR peak amplitude, as suggested in previous studies using the HVSR technique [23][24][25]. Modeling the ambient-noise wavefield, Reference [24] have observed that the amplitude of HVSR peaks also depends on the relative contribution of different types of seismic waves (body and surface waves).…”
Section: Site Characterization-examples From Santo Domingo and Santiamentioning
confidence: 90%